Folklore For Elementary School children’s (Eurasian Scientific Herald, 2024)
Folklore, a traditional form of artistic expression, has been an integral part of human culture for centuries. It is a reflection of a community's history, values, and traditions, passed down from generation to generation through various forms of visual and performing arts. In recent years, there has been a growing recognition of the importance of introducing folklore to elementary schoolchildren. This article argues that incorporating folklore into elementary school curricula can have a profound impact on children's cultural enrichment, creative development, and overall academic performance.